The inquiring mind on intellectual virtues and virtue epistemology - Baehr, Jason S. (Oxford : Oxford University Press, 2011)
Jason Baehr presents a new theory of 'responsibilist' or character-based virtue-epistemology - an approach in which intellectual character traits are given a central and fundamental role.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Virtue epistemology; Intellect